Prevalence and Intensity of Soil-Transmitted Helminths and Associated Factors among Adolescents and Adults in Bibugn Woreda, Northwest Ethiopia: A Community-Based Cross-Sectional Study - Abrham Goshu; Getaneh Alemu; Animen Ayehu (Journal of Tropical Medicine, 2021)
Background. Soil-transmitted helminths are a common public health problem in Ethiopia, affecting all age groups. However, epidemiological studies and interventions primarily target school-age children, despite the fact that 44.6 million adults live in endemic areas. Hence, data on the prevalence and intensity of soil-transmitted helminths infections and associated factors among adolescents and adults helps to expand interventions. Objective. The aim of the study was to assess the prevalence and intensity of soil-transmitted helminths and associated factors among adolescents and adults in Bibugn Woreda, East Gojjam, Northwest Ethiopia. Methods. A community-based cross-sectional study was conducted in Bibugn Woreda from February to September 2021. Using multistage proportionate sampling technique, 641 adolescents and adults were enrolled in this study. Data on sociodemographic characteristics and factors associated with helminthic infections was collected using structured questionnaire prepared in Amharic and administered through face-to-face interview. Parasite detection in stool samples was performed using modified formol-ether concentration and Kato-Katz techniques following standard protocols. Data was entered and analyzed using Statistical Package for the Social Sciences software version 25. Multivariable logistic regression was used to assess factors associated with soil-transmitted helminths infections. P value <0.05 was considered as statistically significant. Results. The overall prevalence of soil-transmitted helminths infection was 20.9% (134/641). The most detected parasite was Ascaris lumbricoides (12.5%), followed by hookworm species (7.5%) and Trichuris trichiura (1.1%). Fecal egg counts revealed that 96.5% (112/116) of the infections were with light parasite intensity, while 3.5% (4/116) were with moderate parasite intensity. Family size >5 (AOR = 1.866; 95% CI: 1.221–2.853; P=0.004), absence of latrine (AOR = 3.675; 95% CI: 1.599–8.449; P=0.002), and no habit of hand washing before meal (AOR = 2.622; 95% CI: 1.073–6.405; P=0.034) were significantly associated with soil-transmitted helminths infections. Conclusion. There was moderate prevalence of soil-transmitted helminths among adolescents and adults with predominance of A. lumbricoides. Family size greater than five, absence of latrine, and no hand washing habit before meal predisposed adolescents and adults for soil-transmitted helminths. The existing school-based interventions should expand to address adolescents and adults.